1995
DOI: 10.1021/bi00001a046
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the catalytic residues lysine 230 and tyrosine 160 in the NADP+-dependent isocitrate dehydrogenase from Escherichia coli

Abstract: Two site-directed mutants of isocitrate dehydrogenase (IDH) of Escherichia coli have been studied by site-directed mutagenesis kinetic and structural studies. Substitution of phenylalanine for tyrosine at position 160 (Y160F) showed 0.4% of the kcat of wild-type with isocitrate as substrate, while the Km for isocitrate remained unchanged. When the postulated intermediate, oxalosuccinate, was enzymatically decarboxylated, Y160F showed a higher kcat and a similar Km to the wild type values. The rate of reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
5
42
1
1
Order By: Relevance
“…In the E. coli IDH structure, the analogous residue is Tyr-160, the side chain hydroxyl group of which makes a hydrogen bond to one of the substrate carboxylate groups and to the guanidinium nitrogen of Arg-153, the arginine residue equivalent to Arg-135 in IDH2. The ability to form these hydrogen bonds has been shown to be critical for proper substrate binding, as a Y160F mutant is inactive (36). It should be noted that citrate is not bound in the catalytic site in these structures.…”
Section: Resultsmentioning
confidence: 95%
“…In the E. coli IDH structure, the analogous residue is Tyr-160, the side chain hydroxyl group of which makes a hydrogen bond to one of the substrate carboxylate groups and to the guanidinium nitrogen of Arg-153, the arginine residue equivalent to Arg-135 in IDH2. The ability to form these hydrogen bonds has been shown to be critical for proper substrate binding, as a Y160F mutant is inactive (36). It should be noted that citrate is not bound in the catalytic site in these structures.…”
Section: Resultsmentioning
confidence: 95%
“…The phenolic side chain of Tyr125 occupies a position totally different from those of the corresponding Tyr residues in TfIPMDH and EcICDH. Nevertheless, the Tyr125Ala mutation caused a substantial decrease in the k cat value, as do corresponding mutations in EcICDH (Tyr160) and TtIPMDH (Tyr140) (11,15,21). This result suggests that Tyr125 is involved in the catalytic function of TtHICDH.…”
Section: Discussionmentioning
confidence: 91%
“…There is discrepancy in the IDH activity of the R132H mutant as Zhao et al [12] showed a 2-fold decrease in the catalytic rate while Dang et al [13] reported a 1000-fold reduction, and our data are in better agreement with that reported by Zhao et al In addition, the kinetic parameters of the R132C, R132S, and R132L mutants are similar to that of the R132H mutant ( Table 2). The Y139A and K212A mutants display < 1% activity ( Table 2), indicating that Tyr139 and Lys212, like their counterparts in EcIDH and PmIDH [22,25,27], play critical roles in the catalytic reaction. Our data also show that mutations D252A and D275A have severe effects on the K m and/or k cat due to their involvements in both ICT binding and catalysis (Table 2).…”
Section: Kinetic Studies Of the Wild-type And Mutant Idh1mentioning
confidence: 99%